A coupling method of response surfaces (CRSM) for cutting parameters optimization in machining titanium alloy under minimum quantity lubrication (MQL) condition - Liu, ZhiQiang; Xu, Jinyang; Han, Shu; Chen, Ming (International journal of precision engineering and manufacturing, 2013)
This paper presents a new flexible method referring to coupling response surface methodology (CRSM) to acquire optimum cutting parameters in machining of difficult-to-cut titanium alloy under minimum quantity lubrication (MQL) condition. Cutting speed, feed rate and depth of cut are designed as three factors by using the Taguchi method, which are also subject to several constraints including processing efficiency, cutting force and surface quality. In addition, turning experiments of titanium alloy were performed in order to set up the model based on Taguchi experimental design and multiple regression method. ANOVA was carried out to prove the adequacy of the developed mathematical model and the influences of cutting parameters on constraints were also observed. The results indicated that the feed rate was the dominant factor affecting surface roughness and cutting forces, which were minimized when the feed rate and depth of cut were set to the lowest level, while cutting speed was set to the highest level. Moreover, the predicted values obtained by CRSM were in good agreement with the experimental values, which indicated that CRSM was an effective method to determine optimum cutting conditions for machining process under MQL condition.